Analisis Pengaruh Firm Size dan Likuiditas Saham Terhadap Fenomena Market Overreaction di Bursa Efek Indonesia - , DANES QUIRIRA O ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis examines anomalies that occur on the Indonesia Stock Exchange . The anomaly is characterized by return reversal . The anomaly is market overreaction and size effect . The author also adds a new variable, such as stock liquidity which has purpose to examine the influence of the level of investor favorability of stocks market anomalies phenomena. The research used samples of stocks that enter at the KOMPAS 100 index from January 2010. KOMPAS Index 100 stocks chosen for the entry in the index is active stocks and provide a great influence on the movement Composite Stock Price Index ( CSPI ). Stocks are grouped into the sample into two portfolios, winner portfolio and loser portfolio. Both portofolio is formed by rating system. Forty stocks that have the highest ratings on portfolios grouped winner , while the forty lowest stock portfolios grouped on the loser . Both portfolio performance is observed in the test period of 6 months, 1 year , 1.5 years , 2 years and 2.5 years and is compared its performance with formation period by t â test method . To know significant level firm size and liquidity of stock effect. the authors use regression methods . The dependent variable of regression function is abnormal portofolio return , while the independent variable are firm size and stock liquidity Results of the study is suggested that there was a market overreaction occurred only in loser portfolios . Firm size is only significant in the loser portofolio , but the direction is positive. In the liquidity of the stock , there is no significant effect on both the portfolio .